Synthesis, Crystal Structures and Magnetic Properties of Mononuclear High-Spin Cobalt(II) Complex - Mohd. Muddassir; You Song (Crystals, 2020)
A new four-coordinated high-spin Co(II) complex was synthesized through the reactions of Co(NSC)2 with bathocuproine, by the diffusion method, resulting in an infinite one-dimension chain. Both static and dynamic magnetic properties were measured. The magnetic properties investigation shows that the single CoII ion properties dominate the magnetic behavior in the complex. Despite the presence of a four-coordinated single CoII ion, no SMM properties were exhibited by the complex.